Analisis Unsur Intrinsik Dalam Komik Lookism Karya Park Tae-Jun - Levi Al Kausar; Siti Muslimah; Ruliyani Ruliyani; Anwarsani Anwarsani; Siti Rahmawati; Nabila Salwa (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The comic "Lookism," is a narrative that follows the journey of Park Hyung Seok, a teenager who experiences bullying because of his appearance. His decision to change houses and schools brings about a drastic transformation when he wakes up with a perfect new body. Despite gaining a popular social life at a new school, Park Hyung Seok is still faced with the challenge of adapting to changes in his body and environment. The uniqueness of this story lies in the ability to return to one's original body, reminding that physical appearance is not everything. The main message of "Lookism" is the importance of self-acceptance and the realization that success in life does not only depend on appearance, but also on personality and abilities. This comic illustrates that every change brings new adventures. Life is a journey full of mysteries and challenges that shape a person's character. The comic "Lookism" teaches that true happiness and success in life lies in self-acceptance and the development of true personality and abilities.